Transformations of administration law in the Postmoderne State - Model of Public function law - - Benouarzag, Hicham; Benarab, Mohamed (Journal of Human Sciences, 2021)
The new transformation of the post-modern state obliges to renew the methods of the civil service, to apply the indices of efficiency and to improve the relation between the state and the citizen. These notions required research on efficiency, competence, expediency, modernity, to ensure performance.These approaches lead to radical changes at the levels of administrative law and mainly on the legal organization of the public service, through the insertion of good private sector practices at the levels of the legal framework of the public service